Controlled growth of hexagonal Zn2GeO4 nanorods on carbon fibers for photocatalytic oxidation of p-toluidine. Issue 33 (11th March 2015) - Jiang, Guohua; Tang, Bolin; Chen, Hua; Liu, Yongkun; Li, Lei; Huang, Qin; Chen, Wenxing
Abstract : Hexagonal Zn2 GeO4 nanorods grown on the surface of carbon fiber substrates have been prepared for photocatalytic oxidation of p -toluidine. Abstract : In this paper, hexagonal Zn2 GeO4 nanorods grown on the surface of carbon fibers (CFs) that were pre-activated by sodium hypochlorite were prepared by a facile solvothermal method. The possible growth mechanism has been investigated by theoretical calculations and a simulation experiment by growth of Zn2 GeO4 on a 2D flat surface of graphene. The (113) crystal facet of Zn2 GeO4 nanorods attached to the CFs surface was the most stable structure. Due to the synergistic effect between the photocatalytic activity of Zn2 GeO4 and excellent adsorption capacity of CFs, the resultant Zn2 GeO4 /CFs composites exhibited excellent photocatalytic activity for oxidation of p -toluidine.